Answer:
(x - 6)(x + 3)
Step-by-step explanation:
Given
x² - 6x + 3x - 18 ( factor the first/second and third/fourth terms )
= x(x - 6) + 3(x - 6) ← factor out (x - 6) from each term
= (x - 6)(x + 3)
First multiple of 4 is x = 144
Second multiple of 4 is x + 4 = 144 + 4 = 148
Third multiple of 4 is x + 8 = 144 + 8 = 152
The answer is a i think but if u get it wrong im sorry
Answer:
x = 2, y = -1.
Step-by-step explanation:
2x + y = 3
x - y = 3
Adding the 2 equations eliminates y:
3x = 6
x = 2.
Substitute for x in the first equation:
2(2) + y = 3
y = 3 - 4
y = -1.
Check the results by substitution in equation 2:
2 - (-1)
= 2 + 1 = 3 .
Checks OK.
She will nee 391 square feet of flooring at $13.59: $5313.69